57=5(1-x)+4(-2+5x)

Simple and best practice solution for 57=5(1-x)+4(-2+5x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 57=5(1-x)+4(-2+5x) equation:



57=5(1-x)+4(-2+5x)
We move all terms to the left:
57-(5(1-x)+4(-2+5x))=0
We add all the numbers together, and all the variables
-(5(-1x+1)+4(5x-2))+57=0
We calculate terms in parentheses: -(5(-1x+1)+4(5x-2)), so:
5(-1x+1)+4(5x-2)
We multiply parentheses
-5x+20x+5-8
We add all the numbers together, and all the variables
15x-3
Back to the equation:
-(15x-3)
We get rid of parentheses
-15x+3+57=0
We add all the numbers together, and all the variables
-15x+60=0
We move all terms containing x to the left, all other terms to the right
-15x=-60
x=-60/-15
x=+4

See similar equations:

| 1x/4-6=x+9 | | -8p=-6(p+2) | | 110=0.60x=40+0.70x | | |n-9|=4 | | 5x/2)-6=2x-7/6 | | 8x=47+8(x+5) | | 2(u-4)=2u+1-3(-6u-2) | | 19=1.08(t/23) | | -3(4u-4)+8u=5(u+3) | | 8x+5=6x=11 | | 4(t+30)=5-3t | | 7f−6=–6+7f | | (1/6x)-(2/3)=(1/2x)-(5/6) | | 4y+4=5y-8 | | 5(u-7)-3=-4(-6u+6)-u | | (1/6)x(-2/3)=(1/2)x(-5/6) | | 5q-3=1-6q | | x+4(x+50)=40 | | 3x+4=2x+22 | | -2(y+2)=5y+31 | | (4/9)x2-(4/3)x=-1 | | -136=5x-3(1+8x) | | 4w-37=9(w-8) | | 3x10=5x-2 | | x9+5x=3x+13 | | b-9+6b=5 | | 6m²=600 | | 6x3/4+5=7 | | 7x−10−2x=5x+3 | | 28=7x-10+x+3+9x-11 | | 3(2x+3)4x+2=21 | | 5–x=25 |

Equations solver categories